Nghiên cứu và áp dụng các biện pháp kỹ thuật để sản xuất cam xuất khẩu - Đỗ, Đình Ca (2011)
Tác giả: Đỗ Đình Ca; Nguyễn Thị Chắt; Nguyễn Đình Tuệ; Nguyễn Thì Nhậm; Phạm Minh Cường -- Từ khóa: Cam; Sâu hại cam